Digital accessibility of smart cities - tourism for all and reducing inequalities: Tourism Agenda 2030 - Fernández-Díaz, Elena; Jambrino-Maldonado, Carmen; Iglesias-Sánchez, Patricia Pilar; De-las-Heras-Pedrosa, Carlos (Emerald, 2022)
Purpose: There is widespread agreement that the tourism sector should address the issue of sustainability. The purpose of this study is to analyze the digital accessibility of the cities awarded as European Capitals of Smart Tourism for their innovative, accessible and sustainable practices by the European Commission. Design/methodology/approach: An analysis of the digital level of accessibility of 50 uniform resource locator (URL) of European cities was undertaken. The analysis followed the international evaluation requirements of the World Wide Web (W3C). Findings: The results show that none of the official Web pages analyzed obtained 100% in relation to the digital accessibility requirements. The main factors that pose barriers to communication and interaction were identified. Practical implications: The paper encourages smart tourism destinations to overcome the challenge of matching both dimensions of accessibility to obtain barrier-free information to ensure cities are inclusive and sustainable in line with Agenda 2030 (sustainable development goal [SDG] 11). Originality/value: The concept of tourism for all receives special attention in the sector, and this notion is reflected in the UN SDGs. However, accessibility has not been extensively analyzed in relation to the cohesion between the digital and the physical dimension. Tourism research tends to focus on accessible experiences within destinations. This paper introduces a new insight into the key issue of digital accessibility, which can promote destination choice and influence the tourism experience.
Keywords: Accesibilidad para minusválidos; Inteligencia artificial; Smart cities; Smart tourism destinations; Web accessibility; WCAG 2.1; Sustainable development goals (SDGs)